Self-Reported Physical Activity and Relations to Growth and Neurotrophic Factors in Diabetes Mellitus: The Framingham Offspring Study. (9th January 2019) - Spartano, Nicole L.; Davis-Plourde, Kendra L.; Himali, Jayandra J.; Murabito, Joanne M.; Vasan, Ramachandran S.; Beiser, Alexa S.; Seshadri, Sudha
Abstract : Aims . Circulating insulin-like growth factor- (IGF-) 1, vascular endothelial growth factor (VEGF), and brain-derived neurotrophic factor (BDNF) levels are often lower in individuals with diabetes mellitus (DM) and are important for repairing vascular and neuronal dysfunction. The purpose of this investigation was to determine the cross-sectional relations of physical activity to circulating concentrations of IGF-1, VEGF, and BDNF in individuals with and without DM. Methods . In 1730 participants from the Framingham Offspring Study examination cycle 7, including those with DM (n = 179, mean age 64 years, 39% women) and without DM (n = 1551, mean age 60 years, 46% women), we related self-reported physical activity variables to circulating concentrations of IGF-1, VEGF, and BDNF using linear multivariable regression models. We also tested for interactions by age. Participants with prevalent cardiovascular disease, stroke, and dementia or taking hormone replacement therapy were excluded. Results . In participants with DM, more ambulatory physical activity was associated with higher IGF-1 levels (β ± s t a n d a r d errorS E = 0.22 ± 0.08, p = 0.009 ), and more total physical activity was related to higher BDNF levels (β ± S E = 0.18 ± 0.08, p = 0.035 ), but physical activity was not significantly related to circulating VEGF. In participants without DM, no associations were observed. Moreover, in the examination of interactions by age, the association of ambulatory physical activity with IGF-1 levels was only observed in older adults with DM (a g e ≥ 60 years, β ± S E = 0.23 ± 0.11, p = 0.042 ) but not in middle-aged adults with DM (a g e < 60 years, β ± S E = 0.06 ± 0.13, p = 0.645 ). Conclusion . Our results suggest that more physical activity is associated with higher circulating IGF-1 and BDNF in participants with DM. These results, dissecting interactions by both age and DM status, may also help to explain some of the inconsistent results in studies relating physical activity to growth and neurotrophic factors.